Pasang Surut Gambuh Pedungan Di Tengah Laju Budaya Global - I Nengah Sarwa; Wardizal (Institut Seni Indonesia Denpasar, 2007)
This article tries to discuss and analyze about the reality of global culture and its implication on traditional performance art. The subject matter of this analysis is the Pedungan Gambuh dance drama, a classical performance, previously a court/palace art, which is thought as the source of the Balinese music and dance drama. Data and facts presented here are drawn from our qualitative research entitled Stream of Pedungan Gambuh dance-drama in the surge of Global Culture. Our research suggests that Gambuh as an entertaining art has recently declined in the rapid flow of Global Culture.